Pengaruh Ukuran Perusahaan Dan Corporate Social Responsibility Terhadap Manajemen Laba Pada Perusahaan Manufaktur Sub Sektor Otomotif Yang Terdaftar Di BEI Tahun 2017-2020 - Defy Aryanti; Hasim As'ari (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
This study aims to examine the effect of company size and corporate social responsibility on profit management in automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. This type of research is quantitative research. Data collection was carried out using secondary data in the form of annual reports on companies in the automotive and component industry sub-sectors listed on the Indonesia Stock Exchange for 2017-2020 obtained from the Indonesian Stock Exchange website www.idx.co.id. The classic assumption test proves that the data is normally distributed, free of heteroscedasticity and multicollinearity and there is no autocorrelation. The analysis technique used is Multiple Linear Regression Analysis. The results of testing the hypothesis that has been used using the Multiple Linear Regression Analysis formula show that (1) Company size has no significant effect on Earnings Management (2) Corporate Social Responsibility has no significant effect on Earnings Management. It is hoped that further research will examine more samples of manufacturing companies listed on the IDX and examine more of the factors that influence earnings management besides company size and CSR. These factors include Good Corporate Governance, Profitability, Leverage, Audit Quality and others. This research is expected to be used as a company measure, and Corporate Social Responsibility is an important factor in earnings management. It is used as a benchmark in making the right decisions by investors both in investment, credit and others.